Tectonics and Technical Language. Development of and Research on a Language-Sensitive Learning Design on Plate Tectonics - Wey, Santina; Gölitz, Dietmar; Schubert, Jan Christoph (The European Conference on Language Learning 2020. Official Conference Proceedings, 2020)
Results of international studies such as PISA and PIRLS indicate that there is a substantial correlation between language competencies, socio-economic background, and knowledge. At secondary schools, language requirements increase due to a higher level of technical language. As a result, access to subject-related learning becomes more difficult, especially for pupils with low socio-economic status or a migration biography. To give these groups of pupils equal educational opportunities, a learning design for language-sensitive teaching in the Geography classroom was developed. Research and development aspects were intertwined within the framework of design-based research. Firstly, design-frameworks were developed based on the current state of research and then transferred to a six-hour teaching unit on plate tectonics for middle school pupils, which was accompanied by research. The results of the first cycle (N=135) led to a re-design and a second cycle (N=185). To evaluate the language-sensitive unit empirically, the treatment was contrasted with a control group in a pre-post-follow-up design. Both groups covered the same content in the same period. Knowledge, technical language, and motivational aspects were measured. Learning gain scores were evaluated for validity and differences between the two groups. The results show that the experimental group has significantly higher learning gains (Cohen's d post-pre = .51) regarding geographical knowledge and technical languag